Academic Excellence Awards from Pahang Islamic Religious and Malay Customs Council for Nor Suhadah and Nur Aznah - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
GAMBANG, 21 October 2023 – Being active in various activities at the university in addition to academic excellence netted Nor Suhadah Razali the Academic Excellence Award from the Pahang Islamic Religious and Malay Customs Council at the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Convocation Ceremony, which took place at the Sports Complex Hall, UMPSA Gambang Campus.